Every day deserves a chance : wake up to the gift of 24 hours - Lucado, Max. (Nashville : Thomas Nelson, 2007)
Invites readers to give every day a chance, offering them a delightful formula for upgrading each day to blue ribbon status by saturating their day in Jesus's grace, entrusting their day to His oversight, and accepting His direction.
Every day deserves a chance -- Mercy for shame-filled days -- Gratitude for ungrateful days -- Forgiveness for bitter days -- Peace for anxious days -- Hope for catastrophic days -- Fuel for depleted days -- Faith for fear-filled days -- Calling for purposeless days -- Service for fork-in-the-road days -- The blade of uncommon color.
Includes bibliographical references.
Keywords: Christian life; Christian life